IDENTIFYING THE SKILL GAP IN THE SKILL INDIA COURSE “DIGITAL MARKETING” – A STUDY IN THE NAVI MUMBAI REGION - Sinha, Dr. Mona; Kalse, Anjali; Yadav, Rikhi; Mohanty, Mona (ShodhKosh: Journal of Visual and Performing Arts, 2026)
India’s digital economy is growing at an unprecedented pace, yet a noticeable gap persists between the number of trained graduates and the number of genuinely employable professionals. The Skill India Mission, launched in 2015, was designed to address this challenge by equipping young people with market-relevant vocational skills. Despite these efforts, uncertainties remain about how well its digital marketing courses actually meet industry requirements. This study explores these concerns by examining the “Digital Marketing” course offered under Skill India in the Navi Mumbai region. It evaluates how course content, trainer effectiveness, and pedagogical practices influence employability outcomes. Using a quantitative approach supported by Structural Equation Modelling (SEM), data from 176 students and trainers were analysed to assess the relevance of the curriculum and the quality of training delivery. The results reveal a strong relationship (R² = 0.83) between overall learner satisfaction and three core components: course content, pedagogy, and employability skills. While participants reported gaining a solid conceptual foundation, many also indicated gaps in hands-on campaign execution and analytical skill development. To address these shortcomings, the study recommends incorporating live projects, digital analytics tools, and sustained trainer upskilling into the programme. These insights hold important policy implications for the Skill India Mission. A shift from focusing primarily on certification numbers to prioritising employability outcomes would significantly enhance the initiative’s impact. Strengthening alignment with industry expectations will not only support India’s rapidly evolving digital economy but also advance progress toward Sustainable Development Goal 8: Decent Work and Economic Growth.